Delay-based Reliability Analysis on Construction Projects - Sorooshian, Shahryar (Zhengzhou University, Marsland Press, 2014)
The construction industry has a crucial role in the overall development of any economy; however it has its own drawbacks and difficulties that should be well studied in order to improve the efficiency of this industry. Delays, which are an inseparable part of any project, are an important issue in construction projects that are responsible for huge losses in capital investments and slow-moving progress of this industry. This study tries to investigate delay-based reliability of building construction projects. In order to achieve this goal the related literature is studied and the most common problems in this filed are found. Then, the questionnaire based on the literature and expert’s recommendation is designed to analyze operations risk and industry reliability based on the delay sources. A multi-expert approach group decision making analysis of this research ranks the dominance of controllable factor on the project delays. Finally, based on risk value of delay factors, this research verifies the industry reliability.